Muscle strength in adult patients with chronic kidney failure at the National Hospital and Military Hospital in 2021 - Real Delor, Raúl Emilio; Roy-Torales, Tatiana; Brítez-Mendoza , Jorge David; Encina-Villagra , Domingo Guzmán; Giménez, José Luis; Gómez, Maria José; González Hermosa, Eliana María; Insfrán Cabrera, Nilda Andrea; Mareco Caballero, Valeria Emilia; Pérez Alves, Jessica Shirleni; Ramírez Colmán, Yenniffer Marlene; Ruiz Díaz Ojeda, Elio David; et al. (Medicina Clínica y Social, 2022)
Introduction: muscle strength may decrease in patients with chronic kidney failure due to various causes. Objective: to determine the anthropometric and clinical variables and muscle strength in adult patients with chronic kidney failure. Methodology: an observational, descriptive, cross-sectional design was applied. Men and women, older than 17 years, with chronic kidney failure who attended the National Hospital (Itauguá) and Military Hospital (Asunción), Paraguay, between April and November 2021 were included. Anthropometric, clinical and laboratory variables were determined. Muscle strength was measured with a hand dynamometer. A group of healthy young subjects was used as a control group for the comparison of muscle strength. Descriptive statistics were applied with the statistical program Epi Info 7 ™. The research was approved by the Ethics Committee of the Universidad Privada del Este, Paraguay. Results: 119 subjects entered the study, being 62 (52%) males with a mean age 56 ± 15 years and 57 (48%) females, with a mean age 51 ± 16 years. The mean creatinine clearance was 16.4 ± 17.9 mL / min. The most common etiology was the association of arterial hypertension and diabetes mellitus (45%). The control group included 99 women with a mean age 25 ± 5 years and 51 men with a mean age 26 ± 5 years. When comparing strength between patients and healthy subjects, 66.4% decreased muscle strength was found among patients with chronic renal failure. Conclusion: muscle strength is decreased in 66.4% of chronic kidney failure patients. Early detection and early treatment of muscle strength deficit is recommended in this group of patients.